Persepsi masyarakat terhadap upaya pelestarian kesenian bantengan di kabupaten Malang - Rochiyana, Luluk (Maliki Interdisciplinary Journal, 2025)
Bantengan art is a cultural heritage that is rich in historical and traditional values ​​in Malang Regency. In the context of modernization and globalization, efforts to preserve this art have become increasingly important but also full of challenges. This research aims to explore public perceptions of efforts to preserve Bantengan art in Malang Regency. A qualitative approach was used with in-depth interview methods and participant observation. Data was collected from ten sources consisting of Bantengan artists, community leaders and local residents. The research results show that the community has a high awareness and appreciation of the importance of preserving Bantengan art. Support from the government and local communities is considered significant, although challenges such as low interest from the younger generation, limited funds and inadequate infrastructure are still the main obstacles. To overcome this challenge, the integration of digital technology and improvement of supporting facilities are proposed as solutions. This research concludes that intensive collaboration between the government, local communities and the younger generation is very necessary to ensure the sustainability of Bantengan art as a cultural heritage that can be passed on to future generations.